Molecular Epidemiology and AMR Perspective of Diarrhoeagenic Escherichia coli in Africa: A Systematic Review and Meta-analysis - John Bosco Kalule; Linda A. Bester; Daniel L. Banda; Firehiwot Abera Derra; Chisomo Msefula; Anthony M. Smith; Abraham Ajayi; Happiness Kumburu; Geoffrey Kwenda; Kaunda Yamba; John Mwaba; Yasmina J. Fakim; et al. (Journal of Epidemiology and Global Health)
Abstract Introduction Diarrhoeagenic Escherichia coli (DEC) persistently challenges public health in Africa, contributing substantially to the diarrhoeal disease burden. This systematic review and meta-analysis illuminate the distribution and antimicrobial resistance (AMR) patterns of DEC pathotypes across the continent. Methods The review selectively focused on pathotype-specific studies reporting prevalence and/or AMR of human-derived DEC pathotypes from African nations, excluding data from extra-intestinal, animal, and environmental sources and studies focused on drug and mechanism experiments. Pertinent studies were retrieved from SCOPUS, PubMed, and EBSCOhost, processed with Covidence, and screened in alignment with PRISMA guidelines. Results The reviewed studies were predominantly hospital-based (80%) and paediatric-focused (91%), with a meagre 4.4% documenting DEC outbreaks. Seven DEC pathotypes were discerned, with Enteroaggregative E. coli (EAEC) being notably prevalent (43%, 95% CI 30–55%) and Enteroinvasive E. coli (EIEC) least prevalent (24%, 95% CI 17–32%). Identified non-susceptibilities were noted against essential antibiotics including ciprofloxacin, ceftriaxone, and ampicillin, while instances of carbapenem and Extended-Spectrum ß-Lactamase (ESBL) resistance were scarce. Conclusion Despite sporadic data on DEC prevalence and AMR in Africa, particularly in community settings, a palpable gap remains in real-time outbreak surveillance and comprehensive data documentation. Augmenting surveillance and embracing advancements in molecular/genomic characterisation techniques are crucial to precisely discerning DEC's actual impact and resistance continuum in Africa.